TEXT MESSAGE FLOW MODEL OF THEMATIC INTERNET RESOURCES INFORMATION SECURITY FORECASTING SYSTEMS - DZHULIY, Volodymyr; PETLIAK, Natalia; KHMELNYTSKYI, Yuri; PAKHAR, Oleksandr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The tasks of analysis and classification of detection of existing mechanisms for the implementation of attacks and threats to information security, which can lead to unauthorized access to confidential information, disruption of the functioning of information systems, are relevant and prioritized at the current stage. The importance of the problems is connected with the following main factors: growth of variety and quantity of means of computer technology and spheres of human activity; a high level of trust in information and search systems for data processing and management; the growth of the number of users of the information space of interaction; accumulation of large volumes of various types of information, intensive exchange of data flow in the network between users, using a wide range of access mechanisms to confidential resources, information processes; industrial espionage and competitive struggle in the sphere of information services of society; insufficient number at the present stage of highly qualified specialists in the field of information security, market relations in the field of software development, maintenance, distribution, production of computing equipment for the implementation of information security. The presented model of the flow of text messages of thematic Internet resources of the information security forecasting system and the information model of the forum database of the thematic Internet resource, which differs from the known ones in its universality, allows to analyze and study the data flow of Internet forums implemented on the basis of popular software platforms for the development of discussion information thematic resources The model of the flow of text messages of thematic Internet forums allows statistical analysis and semantic filtering of messages, taking into account authorship, author rating, forum, time of creation, number of messages, forum topic, allows analysis and research of text messages of thematic Internet resources. Solving the set tasks will allow: to improve the quality of decisions made in the process of identifying and counteracting malicious information; sort information objects of influence for the operator by priority; set the input data settings of the system of detection and countermeasures against the spread of malicious information in networks.